Analisis Potensi Energi Angin Menggunakan Turbin Horizontal di Kawasan Wisata Mangrove Desa Tanjung Rejo, Kecamatan Percut Sei Tuan - Idris, Muhammad; Zulfikar, Achmad Jusuf; Darianto, Darianto; Iswandi, Iswandi; Jufrizal, Jufrizal; Hermanto, Tino; Haniza, Haniza; Harahap, Uun Novalia (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
The tridharma of higher education is the main task and function for every lecturer that must be carried out every semester. One of the activities of the tridharma of higher education is community service which aims to make a scientific contribution owned by each lecturer. On this occasion, the UMA mechanical engineering study program had the opportunity to carry it out in Tanjung Rejo village, Percut Sei District. The master who owns the mangrove forest tourist attraction. The tourist attraction is located on the coast of the Strait of Malacca, where geographically it has the potential for renewable energy, namely wind energy. Based on the measurement data, the average wind speed was obtained 2 m/s. From the potential power that can be generated through a horizontal type wind turbine theoretically 59.8 W. Actually, this turbine has an average power of 20.9 W. This difference occurs due to an efficiency factor of 35%. The potential of wind energy in Tanjung Rejo Tourism Village is very promising for development. This effort will not only increase the energy independence of the village, but also reduce carbon emissions and preserve the environment.